A conventional strabismus surgical approach for lost medial rectus muscles. (December 2013) - Altinsoy, Halil Ibrahim; Ceylan, Osman Melih; Mutlu, Fatih Mehmet; Gokce, Gokcen
Abstract We present 3 cases of successful conventional strabismus surgery to retrieve lost medial rectus (MR) muscles. In all cases the lost MR muscle was retrieved and re-attached to the intended scleral point. Two patients had residual exotropia, while the third case was orthophoric after surgery. The retrieval of lost MR muscle using conventional strabismus surgery technique can be successfully achieved if the lost MR muscle is recognized early and the re-operation is performed by an experienced surgeon.